2015
DOI: 10.1007/s00894-015-2648-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of carbon monoxide on the pristine, B- and Al-doped C3N nanosheets

Abstract: The potential application of the intrinsic and extrinsic (8,0) zigzag single-walled C3N nansheets as chemical sensor for CO molecules has been investigated using density functional theory calculations. The calculation shows that the pristine sheet is a semiconductor with a HOMO-LUMO gap (Eg) of about 2.19 eV. The pristine and B-doped sheets can weakly adsorb a CO molecule with the adsorption energies of -4.8 and -4.6 kcal mol(-1), and their electronic properties are not sensitive to this molecule. By replacing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(22 citation statements)
references
References 34 publications
3
19
0
Order By: Relevance
“…The calculated lattice constant of C 3 N is 4.861Å, which agrees closely with the experimental value of 4.75 Å . The CC( d CC ) and CN ( d NC ) bond lengths are 1.404 and 1.403 Å, respectively, which agree well with previous calculations . The total and difference charge densities are also shown in Figure a.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The calculated lattice constant of C 3 N is 4.861Å, which agrees closely with the experimental value of 4.75 Å . The CC( d CC ) and CN ( d NC ) bond lengths are 1.404 and 1.403 Å, respectively, which agree well with previous calculations . The total and difference charge densities are also shown in Figure a.…”
Section: Resultssupporting
confidence: 89%
“…The calculated lattice constant of C 3 N is 4.861Å, which agrees closely with the experimental value of 4.75 Å. [71,73,75,86] The total and difference charge densities are also shown in Figure 1a. [71,73,75,86] The total and difference charge densities are also shown in Figure 1a.…”
Section: Structure and Electronic Properties Of C 3 Nsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, other DFT studies have shown the ability of Al and Fedoped graphene for adsorption of several classes of pollutants such as p-nitrophenol [21], dioxane [22], acetyl halides [23], formaldehyde [24], transition metals [25], and small gas molecules (such as HCN, CO, SO 2 , N 2 O, etc) [26][27][28][29], among others; the doping of other nanostructures as C 3 N nanosheets has proven also to increase the adsorption strength of analites [30]. Note that the dopants in graphene are capable to decrease the structural work associated with the activation energies [31,32]; in addition, Al and Fe atoms improve the binding of the substrate with lone-pair containing adsorbates because they behave as Lewis acids, and these dopants show a low-cost and benign behavior with the environment [28].…”
Section: Introductionmentioning
confidence: 98%
“…Until now, numerous studies have focused on the graphene-like inorganic and all-boron monolayers because they are of great importance as graphenes [33][34][35][36][37][38][39][40][41][42][43]. Since all-boron honeycomb hexagonal networks are electron deficient, it has been found that B atoms cannot generate these kinds of structures [42].…”
Section: Introductionmentioning
confidence: 99%